2012
DOI: 10.1055/s-0032-1306302
|View full text |Cite
|
Sign up to set email alerts
|

Prioritisation in Haemophilia A: A Qualitative Study of Stakeholder Attitudes and Preferences

Abstract: To learn more about prioritisation in the health care system, we performed an exploratory qualitative study on haemophilia A. The aim was to generate haemophilia disease-specific criteria and to learn more about reasoning in the decision-making process. The 40 participants (patients, relatives, physicians, nurses) were asked in semi-structured interviews about their experiences regarding the German health care system in general and the management of haemophilia A. The 4 stakeholder groups agreed that treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…Introduction ▼ Children with severe haemophilia A and inhibitors are an example for patients with a rare disease requiring individualized therapies. Evaluation of German patients', relatives', physicians' and nurses' attitudes towards prioritisation in haemophilia A revealed that major decision-making criteria were maintenance of mobility, social responsibility and the prospect of a long working life span [ 10 ] . Facing the high therapy costs for haemophilia, all measures, which show the potential to improve quality of life in haemophilia patients and to reduce bleeding frequency, should be promoted in the fi rst place [ 27 ] .…”
Section: Treatment Of Children With Severe Haemophilia a And Inhibitomentioning
confidence: 99%
“…Introduction ▼ Children with severe haemophilia A and inhibitors are an example for patients with a rare disease requiring individualized therapies. Evaluation of German patients', relatives', physicians' and nurses' attitudes towards prioritisation in haemophilia A revealed that major decision-making criteria were maintenance of mobility, social responsibility and the prospect of a long working life span [ 10 ] . Facing the high therapy costs for haemophilia, all measures, which show the potential to improve quality of life in haemophilia patients and to reduce bleeding frequency, should be promoted in the fi rst place [ 27 ] .…”
Section: Treatment Of Children With Severe Haemophilia a And Inhibitomentioning
confidence: 99%